Negative Emotional Stimuli Enhance Conflict Resolution Without Altering Arousal - Fehring, Daniel J. (Front Hum Neurosci, 2019)
In our daily life, we frequently need to make decisions between competing behavioral options while we are exposed to various contextual factors containing emotional/social information. We examined how changes in emotional/arousal state influence resolving conflict between behavioral rules. Visual stimuli with emotional content (positive, negative and neutral) and music (High/Low tempo), which could potentially alter emotional/arousal states, were included in the task context while participants performed the Wisconsin Card Sorting Test (WCST). The WCST requires the application of abstract matching rules, to resolve conflict between competing behavioral options. We found that conflict influenced both accuracy and response time (RT) in implementing rules. Measuring event-related autonomic responses indicated that these behavioral effects were accompanied by concomitant alterations in arousal levels. Performance in the WCST was modulated by the emotional content of visual stimuli and appeared as a faster response and higher accuracy when trials commenced with negative emotional stimuli. These effects were dependent on the level of conflict but were not accompanied by changes in arousal levels. Here, we report that visual stimuli with emotional content influence conflict processing without trial-by-trial changes in arousal level. Our findings indicate intricate interactions between emotional context and various aspects of executive control such as conflict resolution and suggest that these interactions are not necessarily mediated through alterations in arousal level.